PENGARUH CHALLENGE STRESSORS DAN JOB COMPLEXITY TERHADAP KREATIVITAS PENGEMUDI OJEK DARING: PERAN PEMEDIASI JOB BURNOUT - Angga Kusuma Wardhana; Handrio Adhi Pradana (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to analyze mediation effect of Job Burnout on the relationship of Challenge Stressors and Job Complexity toward Creativity. This research was conducted quantitatively by using questionnaires as a medium to collect data. The sample size used in this study were online transportation drivers in several regions in Indonesia with total of 125 respondents. The distribution of questionnaire was carried out by survey through online form via Google Form which were shared via social media or directly to respective respondents. The research data were analyzed using linear regression analysis using SPSS version 25 and Sobel’s mediation effect testing. The results showed that Challenge Stressors did not have a positive and significant effect on Job Burnout, Job Complexity had a positive and significant effect on Job Burnout, Job Burnout did not have a negative and significant effect on Creativity, and Challenge Stressors and Job Complexity both had a positive and significant effect on Creativity. However, Job Burnout is not proven to mediate the relationship of Challenge Stressors and Job Complexity on Creativity. In discussion section, the researchers elaborate justification and implication of each relationship of variables in the model.